Universita Karlova records - Univerzita Karlova
Greetings in Latin exchanged between Universita Karlova and Colleges of the Seneca, coordinate institutions in Geneva, N.Y.
University in Prague variously known as Charles University and Universitas Carolina.
Collection material in Latin.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Colleges of the Seneca; Universities and colleges -- Czech Republic -- Prague; Universities and colleges -- New York (State) -- Geneva